Omnichannel Marketing in the Digital Age: Effective Strategies to Reach Multichannel Consumers in Indonesia - Sehani Sehani; Gatot Wijayanto; Arini Novandalina; Yutiandry Rivai; Henni Noviasari (West Science Interdisciplinary Studies, 2023)
A transformational era of consumer behavior has begun with the advent of the digital age, where multichannel brand involvement is the standard. Businesses are progressively implementing omnichannel marketing tactics in Indonesia's dynamic economy to effectively navigate this intricate terrain. In order to find out how well omnichannel marketing techniques work in Indonesia, this study used a mixed-methods approach that included quantitative surveys, qualitative interviews, and content analysis. The results show that omnichannel marketing techniques do, in fact, work, since they significantly influence purchase decisions and generate a high degree of consumer involvement. Customized offers and recommendations strike a powerful chord with Indonesian customers, indicating that personalization is a major success factor. Although omnichannel marketing is generally viewed favorably, worries over data privacy highlight how crucial it is for companies to have open and honest data procedures. Practical suggestions are given for Indonesian businesses to maximize their omnichannel marketing endeavors in light of these findings. This study adds significant understanding to the ever-changing omnichannel marketing scene in Indonesia and provides direction for companies looking to prosper in the digital era while preserving customer confidence and data protection.